Analisis Loyalitas Konsumen Ritel Berbasis Swalayan pada Lab Bisnis - Halilah, Ii; Sari Putri, Ivon Sandya (Jurnal Riset Bisnis dan Investasi, 2016)
The “Lab Bisnis”, which is a Business Administration Dept’s laboratory, is a kind of convenience store. The daily transactions which influence the profit of the store are very low compared with other competitors. This condition might happen because of the low level of customer loyalty. This study found that the customer loyalty factor of Lab Bisnis is high in repeat buying & referrals factors. However, as for the retention behavior, it should be increased by the management. The study can make a module to arrange the loyalty strategy program in next future.